Production of Bioethanol from oil palm empty fruit bunch - Cheng, C.K.; Hajar H. Hani; Ku Syahidah Ku Ismail (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.